Perception of dental surgeons on the ethical and legal aspects of exercising their profession as personal and corporate entities - Mariana Mourão de Azevedo Flores Pereira; Rhonan Ferreira da Silva; Luíza Valéria de Abreu Maia; Ricardo Henrique Alves da Silva; Eduardo Daruge Junior; Luiz Renato Paranhos (Universidade Estadual de Campinas, 2015)
Aim: To evaluate the level of knowledge of dentists of the ethical and legal aspects of exercising their profession as individual and corporate entities; to observe the level of knowledge of professionals on the main taxes inherent to their existence as individual and corporate entities; and to highlight the positive and negative aspects of each entity. Methods: A questionnaire was prepared containing structured and open questions, which was sent to dentists working in the cities of Betim and Contagem (Belo Horizonte metropolitan area) in letters containing self-addressed stamped envelopes for return to the research team. The data were analyzed using descriptive statistics. Results: 77.9% of professionals work as individual entities, 19.7% as individual and corporate entities, and only 2.5% act solely as corporate entities. Of the professionals who work as corporate entities, 88.8% reported that the reason that led them to act as individual and/or corporate entities was a requirement by health plans. With regard to taxes imposed on each type of entity, 67.4% of individual entity professionals declared not knowing the main taxes related to their profession. Conclusions: The level of knowledge of dentists regarding the ethical and legal implications of performing their profession as individual and corporate entities is insufficient; the interviewed professionals are not properly trained on the pertinent ethical and legal aspects of their profession, thus becoming vulnerable to litigation; and these professionals do not have knowledge on the main taxes related to each type of legal entity.